EFL TEACHERS’ BELIEF ON CLASSROOM MANAGEMENT AND BEHAVIOR AS THE KEY SUCCESS OF ENGLISH LANGUAGE TEACHING - Reti Wahyuni (International Conference on Education and Language (ICEL), 2016)
The failure of teaching and learning process is as the result of the failure of managing the class and this becomes the crucial issue as the teachers still ignore to organize or create conducive atmosphere as well through the factors and process of what goes inside of the class. This study is aimed at finding out the teachers’ belief classroom management as the key success of English language teaching. This study employed as a qualitative study which used two data collection techniques; teacher survey and open-ended questionnaire with twelve English teachers in Lampung. After the data being analyzed, the finding revealed that the teachers’ belief of classroom management is as very important aspect of teaching and the process that teachers should deal with in the classroom with their students. The essential belief is that how teachers keep balance among the method and the management itself and the students’ needs can be taken as consideration for taking the strategies. The teachers’ beliefs are changed since they are pre-service teachers because their life experience, teaching experience, reading and professional development, changes in belief and strategies, and necessity to change. The most common annoying student infractions for English teachers have to deal are disturbing other, lazy students in the class, making noisy, bullying, forgetting the lesson, dependent students during the test, asking without raising hand and inappropriate words. The discipline procedures and strategies implemented by English teachers are verbal or non-verbal cues and warnings, establishing class routines, changing teachers’ attitude to routines, punitive behavior management, and conference with students, behavior plan and positively reinforced behavior management strategies and administrative intervention. The further study can be conducted by looking at another aspect in large scope of research and comparing between teachers with their different culture and educational background.